Dynamics of Natural Killer Cells Cytotoxicity in Microwell Arrays with Connecting Channels - Xu, Yuanhao; Zhou, Shufan; Lam, Yun Wah; Pang, Stella W. (Frontiers in Immunology, 2017)
Natural killer (NK) cells serve an important role in immune system by recognizing and killing the potentially malignant cells without antigen sensitization, and could be promising in cancer therapy. We have designed and fabricated microwell arrays with microchannel connections in polydimethylsiloxane (PDMS) substrates to study the interaction dynamics of NK-92MI cells with MCF7 breast cancer cells using time-lapse imaging by fluorescence microscopy for 15 h. Although cell seeding density was the same, NK cell cytotoxicity was found to be higher in larger microwells, which is manifested as increased target death ratio from 13.7±3.1% to 46.3±3.3% and shorter triggering time of first target lysis from 502±49 min to 391±63 min in 150×150 µm2 microwells comparing to 50×50 µm2 wells in 15 h. Mirochannel connection between adjacent microwells of the same size increased the overall target death ratio by >10%, while connection between microwells of different sizes led to significantly increased target death ratio and delayed first target lysis in smaller microwells. Our findings reveal unique cell interaction dynamics such as initiation and stimulation of NK cell cytotoxicity in a confined microenvironment, which is different from population-based study, and the results could lead to a better understanding of the dynamics of NK cell cytotoxicity.